MILITARY AVIATION AND TRAINING PREPARATION IN MONGOLIA - Chogdon Boldbaatar, (International Journal of Innovative Technologies in Social Science, 2025)
The Mongolian people were introduced to aircraft for the first time on May 25, 1925, when pilot A.A. Lapin arrived flying a Yu-13 cargo aircraft. The arrival of the aircraft generated great interest among the city and roadside residents, who gathered to discuss the large, noisy white object flying overhead. In present day Selenge Province, witnesses of the aircraft flying even offered samples of their milk and tea, believing that a god had descended from the sky. During the early years of the revolution, young people actively participated in the movement to acquire aircraft, engaging in propaganda and education efforts that played a crucial role in the important task of mastering new technology and training pilots and technicians.This paper traces the historical development of military aviation and personnel training in Mongolia from 1925 to the present. The introduction of aircraft to Mongolia in 1925 by Soviet pilot A.A. Lapin marked a significant milestone in the nation’s military and technological progress. The study explores the establishment and evolution of Mongolia’s Aviation Force through different historical phases. During the early revolutionary period, youth organizations raised funds to acquire aircraft, with symbolic names like “Revolutionary Party,” “Revolutionary Mongolia,” and “Revolutionary Youth.” The government employed a three-pronged approach to personnel training, utilizing Soviet instructors, establishing aviation schools, and sending students to the Soviet Union.The 1930s saw the Mongolian People’s Revolutionary Army’s Aviation Force grow into a combat-ready unit under key military leaders. The force expanded its fleet and established air routes across Mongolia. Combat experiences in the 1936 battles provided tactical insights. The force played crucial roles in conflicts against Japanese aggression and Xinjiang insurgents, highlighting its strategic importance.In the modern era, specialized squadrons were formed, including the military communications flight squadron, fighter aircraft squadron, and combat helicopter fire support squadron. The Military Communications Flight Squadron undertook diverse missions, including peacekeeping operations. The study also addresses challenges faced, such as political repressions in the late 1930s. Primary historical sources, including anniversary histories and official records, provide a comprehensive overview of Mongolia's aviation development. The dual nature of military and civil aviation development showcases aviation's multifaceted contributions to Mongolia's modernization.